Curves of the second order - as sections of surfaces second order in predetermined parameters - Baidabekov, Ауез; Muradov, Шамид; Adilov, Полат; Tashimov N.E., Ташимов Н.Э. (Рroblems of engineering and professional education, 2023)
In given article are considered ways of the determination position secant planes of the surfaces of the second order of the general type (on example of the ellipsoid with three axises and elliptical parabolic) on circular sections forward given radius